Computational repurposing of polyphenols for anti-Mpoxviral activity - Rishi Vachaspathy Astakala; Gagan Preet; Ahlam Haj Hasan; Ria Desai; Meshari Alfurayh; Rainer Ebel; Marcel Jaspars (In Silico Pharmacology, 2025)
Mpox is a globally prevalent disease that has triggered multiple epidemics over the past few decades, leading to moderate rates of hospitalisation and mortality. Recently, it has re-emerged in several countries, including the Democratic Republic of Congo, and appears to be spreading at an unprecedented pace. The disease is caused by zoonotic double-stranded DNA viruses. Due to its similarities with smallpox, distinguishing between the two can be challenging, though the smallpox vaccine typically provides immunity against Mpox. At the time of writing, no approved treatment for Mpox exists; however, several promising candidates have demonstrated the ability to inhibit viral replication, including resveratrol—a polyphenolic compound found in red wine. This study employs molecular docking and molecular dynamics simulations to assess the effectiveness and stability of nine resveratrol analogues. Additionally, 2D and 3D pharmacophore models were developed for the highest-ranked docked compounds, leading to a composite pharmacophore. A structure–activity relationship analysis was also conducted using these top-performing compounds. The findings suggest that two compounds— ( 9 ) [1,1'-biphenyl]-3,4',5-triol and ( 11 ) {3-hydroxy-5-[2-(4-hydroxyphenyl)ethenyl]phenyl}oxidanesulfonic acid—exhibit strong binding affinity, with compound 11 potentially forming a stable complex with the thymidylate kinase of the vaccinia virus. Graphical abstract